Making Sense of the City: Exploring the Use of Social Media Data for Urban Planning and Place Branding - Santala, Ville; Miczevski, Sandro; Brito, Saulo A de; Baldykowski, Ariane Lao; Gadda, Tatiana; Kozievitch, Nadia; Silva, Thiago H (Anais do Workshop de Computação Urbana (CoUrb); 2017: Anais do I Workshop de Computação Urbana, 2017)
Conventional planning of cities is usually based on surveys and other hard evidence collected and organized by the cities' officials and research institutions. The data is usually collected in certain time intervals and it provides a limited overview to the use of urban space. Social media, including online social networks, make available vast amounts of data which nowadays is easily obtained for various types of analyses. Cities have a chance to explore social media data as a new source to study urban dynamics and complement traditional data used for urban planning. Perhaps the new data sources could also be used to overcome limitations in traditional data used in planning. In this paper, we investigated data available in Untappd, a mobile phone application for sharing beer drinking experiences, in the context of planning and place branding in Curitiba. Curitiba recently announced the creation of a Craft Beer Street, to promote local beers. By using this as a real case study we investigate a new approach that could help creating this kind of attractions, considering the aspects related to place branding as well.